EFFECT OF CELLULOSIC MICRO- AND NANO- SIZED FILLERS ON STRENGTH AND MICROSTRUCTURE OF RUBBER COMPOSITES (Nigerian Journal of Technology, 2024)
The tensile strength of polymer composites is basically influenced by the geometry (size and shape) of the reinforcing material as well as interfacial interaction and bonding between the polymer matrix and reinforcing phase. This work compares the effect of microfillers to nanofillers of coconut husk, bamboo and cotton linter on the tensile strength and microstructure of vulcanized rubber matrix. The various composites were formulated and prepared using filler loading of 5, 10, 15, 20, 25 and 30 parts per hundred of rubber (pphr) in rubber matrix for both micro- and nano- fillers of the various biomass through friction shearing and compression moulding processes. Results revealed that the tensile strength of the nanocomposites predominantly increased from 1.85 MPa for neat sample to maximum values of 3.83, 3.16 and 3.85 MPa respectively for composites with 25pphr of coconut husk cellulosic nanoparticles (NR-CHNC25), 30pphr of bamboo cellulosic nanoparticles (NR-BNC30) and with 25pphr of cotton linter cellulosic nanoparticles (NR-CLNC25) conversely, the tensile strength of their counter microcomposites changes from 1.85MPa for neat sample to maximum values of 1.68, 1.67 and 2.46 MPa for composites with 10pphr of coconut cellulosic microparticles (NR-CHMC10) 15pphr of bamboo cellulosic microparticles (NR-BMC15) and 30pphr of cotton linter cellulosic microparticles (NR-CLMC30) respectively within the loading range employed in this experiment. Scanning Electron Microscope (SEM) images of microcomposites showed cases of microfiller debonding and pull-out from the rubber matrix. Hence the improved tensile strength of nanocomposites over their counterpart microcomposites was attributed to the larger surface area provided by nanofillers for interfacial bonding and effective stress transfer.